Fire from volcanic activity: quantifying the threat from an understudied hazard - Quah, Jia Yong (2024)
Natural hazards can trigger fires that increase the area and severity of impacts beyond that caused by the initiating hazard. For some physical processes, such as earthquake, fires are a well appreciated and studied cascading hazard. However, fire from volcanic activity (FFVA) is a highly dangerous and largely understudied hazard arising from volcanic activity. To demonstrate the potential destructiveness of this hazard, we develop a FFVA ignition probability model underpinned by a widely applicable fault tree, which identifies the mechanisms that can lead to fire ignition from volcanic activity. By assigning values to each node of the fault tree, our model can be used to consider the relative probabilities associated with different fire ignition mechanisms. We couple this ignition probability model with a fire spread model to evaluate hazardous areas and associated impacts caused by FFVA. To demonstrate the applicability of our model, we use an eruption scenario for volcanic ballistic projectiles in the Auckland Volcanic Field (Aotearoa New Zealand). This case study demonstrates the potential for FFVA to compound and greatly increase the impacts caused by other volcanic hazards. We found that fire ignition and spread could increase the damaged area and monetary losses associated with the initiating hazard alone by more than six and five times, respectively. We suggest that more study is needed to better understand, evaluate, and plan for FFVA.